Oxygen octahedral coupling mediated ferroelectric-antiferroelectric phase transition based on domain wall engineering. (1st October 2020) - Geng, W.R.; Guo, X.W.; Zhu, Y.L.; Wang, Y.J.; Tang, Y.L.; Han, M.J.; Feng, Y.P.; Zou, M.J.; Wu, B.; Ma, J.Y.; Hu, W.T.; Ma, X.L.
Abstract: Exotic domain-wall phenomena make ferroelectrics the candidates for nanoelectronics. The local symmetry and structure anomalies at domain walls have raised interest in the unusual functionalities, such as domain wall chirality and conductivity. Especially, the spontaneous lattice distortion and symmetry breaking at domain walls activate them as the location of structural transformation. However, the routes to achieve ferroelectric-antiferroelectric phase transition via ferroelectric domain walls remain challenging, which are important to develop materials for energy storage and conversion. Here, we have observed stepwise antiferroelectric phase transition in strained pure BiFeO3 ultrathin films derived from ferroelectric domain walls. Aberration-corrected transmission electron microscopy observation reveals that the resultant phase transition is mediated by dense 180° domain walls via providing the antiparallel cation displacement, cooperating with the enhanced interfacial oxygen octahedral clamping. First-principles calculations further confirm the critical role of interfacial oxygen octahedral coupling during this transition. These findings report an alternative route for antiferroelectric phase transition. Besides, our results provide fresh insights into functionalities of ferroelectric domain walls and open a venue for developing energy-storage materials based on domain engineering. Graphical abstract: Image, graphical abstract